N-heterocyclic carbene catalyzed homoenolate-addition reaction of enals and nitroalkenes : asymmetric synthesis of 5-carbon-synthon δ-nitroesters - Maji, Biswajit (2013)
Synthesizing synthons: The highly enantioselective title reaction is described. It employs catalytic amounts of N-heterocyclic carbene precursors and transforms a broad range of nitroalkenes, such as nitrodienes, nitroenynes, and nitrostyrenes, through reaction with a broad range of enals, into δ-nitroesters via homoenolate intermediates (see scheme).